“Incidencia de la aplicación del carbonato de calcio (CaCO3) como enmienda química en suelos de las comunidades Canchaguano, El Capulí, La Delicia y Fernández Salvador, pertenecientes al Cantón Montúfar, Provincia del Carchi”. - Males Fuertes, Jaime Floresmilo (2019)
SUMMARY The present work is a bibliographical investigation, in order to determine the effect of the application of calcium carbonate (CaCO3) as chemical amendment in the soil, considering that the Montúfar canton of the province of Carchi, is an eminently agricultural area; where acid soils are found and with high organic matter contents. This investigation allowed us to review the elements that make up the soil and its various chemical reactions that occur in the soil solution, as well as the various reactions generated by the incorporation of calcium carbonate in the soil. In order to know the current status of the soils considered in the present study, soil sampling was carried out at four sites: Canchaguano, La Delicia, Capulí and Fernández Salvador; It was sent to the laboratory for a complete analysis of fertility needs. With the results, the CaCO3 needs were calculated in each site studied. Finally, it is concluded that the needs of calcium carbonate for the soils of the Montúfar area is 1.1Tn / ha / year, with the purpose of improving the fertility conditions of the soils and to increase the production of the arable areas of the canton. A plicate for the natural research. Keywords: Carbonate, calcium, soil, cultivable, production, agricultural, compound, chemicals, conservation